Certain biochemical studies on the uterine flushings of normal and endometritis cows - RAVI KUMAR, B P; DEVRAJ, M; JAYAKUMAR, K (The Indian Journal of Animal Reproduction, 2007)
The biochemical parameters viz. pH, alkaline phosphatase (ALP) and total protein in the uterine tlushings of estrus cows with endometritis (n=72) and normal cows (n=l2) were studied. The ph, ALP and total protein in the uterine tlushings were higher (P<0.01) in cows with endometritis. These findings can be used to predict subclinical endometritis.